2019
DOI: 10.3847/1538-4357/aafb6a
|View full text |Cite
|
Sign up to set email alerts
|

Observational Predictions for Sub-Chandrasekhar Mass Explosions: Further Evidence for Multiple Progenitor Systems for Type Ia Supernovae

Abstract: We present a numerical parameter survey of sub-Chandrasekhar mass white dwarf (WD) explosions. Carbon-oxygen WDs accreting a helium shell have the potential to explode in the sub-Chandrasekhar mass regime. Previous studies have shown how the ignition of a helium shell can either directly ignite the WD at the core-shell interface or propagate a shock wave into the the core causing a central ignition. We examine the explosions of WDs from 0.6 -1.2 M ⊙ with helium shells of 0.01, 0.05 and 0.08 M ⊙ . Distinct obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
368
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(399 citation statements)
references
References 45 publications
22
368
3
Order By: Relevance
“…(iv) However, a comparison of our sample in the ∆m 15 v Si ii plane to numerical predictions for double-detonation explosions (Polin et al 2019) revealed that there are two distinct subgroups. The SNe that fall uniformly above the sub-Chandrasekhar double-detonation explosion model predictions line display higher polarization degrees of the Si ii line compared to a distinct "cluster" of normal Chandrasekharlike SNe (see Figs.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…(iv) However, a comparison of our sample in the ∆m 15 v Si ii plane to numerical predictions for double-detonation explosions (Polin et al 2019) revealed that there are two distinct subgroups. The SNe that fall uniformly above the sub-Chandrasekhar double-detonation explosion model predictions line display higher polarization degrees of the Si ii line compared to a distinct "cluster" of normal Chandrasekharlike SNe (see Figs.…”
Section: Discussionmentioning
confidence: 72%
“…15a); and those that are suggested to be sub-Chandrasekhar mass white dwarfs (and fall above the prediction, green diamonds). Interestingly, the supernovae with higher polarization of the Si ii line tend to lie above the numerical ∆m 15 -v Si ii predictions for sub-Chandrasekhar mass explosions by Polin et al (2019), compared to supernovae in the "cluster", below the ∆m 15v Si ii line (Fig. 15a), that have lower polarization degrees of the Si ii line.…”
Section: Double-detonation Modelmentioning
confidence: 74%
See 2 more Smart Citations
“…Simulations of the double detonation of a helium shell on the surface of a WD predict an unusually red excess well before peak luminosity (Noebauer et al 2017;Maeda et al 2018;Polin et al 2019), which were observed in SN 2016jhr (Jiang et al 2017) and SN 2018byg (De et al 2019). Should the SD channel hold, a collision between the SN ejecta and the stellar companion will give rise to strong ultraviolet (UV) emission at early times (Kasen 2010;Hayden et al 2010a).…”
Section: Introductionmentioning
confidence: 97%